Aggregation‐Induced Emission: Aggregation‐Induced Emission: Lighting up Cells, Revealing Life! (Small 47/2016). Issue 47 (December 2016) - Wang, Yi‐Feng; Zhang, Tingbin; Liang, Xing‐Jie
Abstract : Recent advances in aggregation‐induced emission (AIE)‐based probes for biomedical imaging are summarized by X.‐J. Liang and co‐workers on page 6451. AIE probes have recently been considered as alternatives in the area of biological imaging, e.g. lighting up subcellular organelles, tracking cellular processes, monitoring living tissues, improving the diagnosis of disease, and evaluating therapies, to reveal the mysteries of life.